A Facile Synthetic Strategy for Decavanadate and Transition Metal Based All‐Inorganic Coordination Polymers and Insights into Their Electrocatalytic OER Activity. Issue 9 (3rd February 2022) - Kar, Aranya; Sharma, Lalita; Kumar, Akash; Halder, Aditi; Pradeep, Chullikkattil P.
Abstract: This study reports a facile synthetic strategy for decavanadate ([V10 O28 ] 6− ) cluster‐based all inorganic coordination polymers (CPs) containing earth‐abundant and redox‐active transition metals and their electrocatalytic oxygen evolution reaction (OER) activity. The first series of such isomorphous compounds containing the transition metals Mn, Co, and Ni, (H2 O)2 K‐μ‐(H2 O)3 Mn(H2 O)3 2n [V10 O28 ]n (1), (H2 O)2 K‐μ‐(H2 O)3 Co(H2 O)3 2n [V10 O28 ]n (2) and (H2 O)2 K‐μ‐(H2 O)3 Ni(H2 O)3 2n [V10 O28 ]n (3), have been synthesized and structurally characterized. In these polymeric compounds, the [V10 O28 ] 6− clusters are interlaced and inter‐connected by (H2 O)2 K‐μ‐(H2 O)3 ‐M(H2 O)3 +3 units leading to a linear chain‐like arrangement. Each of such chains is further interconnected to adjacent chains by bonding K + ions with a [V10 O28 ] 6− cluster of the adjacent chain leading to a two‐dimensional (2D) sheet‐like arrangement. Hydrogen bonding interactions between the coordinated water molecules and the cluster oxygens further interconnect the adjacent sheets. All these compounds 1–3 are shown to catalyze the oxygen evolution reaction (OER) under alkaline (0.1 M KOH) conditions. Among the three, the Ni‐based catalyst 3 exhibited the best OER activity with a moderate overpotential of 270 mV at onset, a low Tafel slope of 89 mV dec −1, and a turnover frequency (TOF) of 7.5 s −1, which is comparable to similar Keggin POM‐based systems reported so far. The CPs were not highly stable under the OER conditions employed. The post‐catalytic analyses indicated the 'precatalyst' nature of these compounds in alkaline media forming V‐doped metal oxyhydroxides as the OER active species under the turnover conditions. Thus, this study provides a new and facile strategy for synthesizing [V10 O28 ] 6− cluster and transition metal‐based all‐inorganic CPs and insights into their OER electrocatalytic activities for the first time. Abstract : A facile and hassle‐free approach for synthesis of three decavanadate and transition metal (Mn/Co/Ni) based coordination polymers have been reported along with exploration of their activity for electrocatalytic OER as precatalysts in alkaline medium, where in‐situ formed TM based oxyhydroxides proved to be true catalysts.